Pengaruh Orientasi Kewirausahaan, Pemilihan Lokasi Usaha, dan Karakteristik Wirausaha terhadap Keberhasilan Usaha pada Warung Madura di Jember - Farha, Auva Novia; Fatimah, Feti; Rusdiyanto Rusdiyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Warung Madura is one form of micro-enterprise that plays a significant role in supporting the local economy in Jember City. However, the success of this business still faces complex challenges, ranging from competition with modern retail outlets to limitations in capital and business strategies. This study aims to analyze the influence of entrepreneurial orientation, business location selection, and entrepreneurial characteristics on the business success of Warung Madura. The research method employed is quantitative with a descriptive-associative approach, involving 100 respondents who are owners of Warung Madura selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results show that both partially and simultaneously, the three independent variables—entrepreneurial orientation, business location, and entrepreneurial characteristics—have a significant influence on business success. These findings indicate that a combination of entrepreneurial mindset, strategic location selection, and strong personal traits of entrepreneurs are the key factors in promoting the sustainability and growth of Warung Madura amid an increasingly competitive market environment.